Computational Thinking for Youth and Adults Education: Towards a Socially Aware Model - Ortiz, Júlia dos Santos Bathke; Pereira, Roberto (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE), 2020)
Research on Computational Thinking has been growing over the last years, mainly focusing on Elementary and High School students. Challenging audiences, such as Youth and Adults Education, are rarely addressed or even cited in current literature. This Master's research investigates Computational Thinking as a way to promote digital inclusion and proposes a model to design and conduct initiatives for Youth and Adults Education taking into account the characteristics and particularities of this public. The model, with a set of principles and practices, was applied and analyzed in an exploratory case study inside a public school. Results suggest the model is promising to inspire practices to develop Computational Thinking for inclusion. As additional contributions, activities applied in a real setting and lessons learned from their application are presented to support and inform further initiatives.